Leader Polarity‐Reversal Feature and Charge Structure of Three Upward Bipolar Lightning Flashes. Issue 17 (12th September 2018) - Shi, Dongdong; Wang, Daohong; Wu, Ting; Thomas, Ronald J.; Edens, Harald E.; Rison, William; Takagi, Nobuyuki; Krehbiel, Paul R.
Abstract: We have analyzed three upward bipolar lightning flashes (UBLFs) that occurred in Japanese winter thunderstorms. Leader polarity‐reversal processes in three flashes share the same features. During the several tens of milliseconds (lightning A 56 ms, lightning B 21 ms, lightning C 67 ms) before the initiation of the polarity‐reversal leader, one branch of the preceding leader in bipolar flashes was nearly decayed while other branches of the preceding leader were still in propagation. Then the polarity‐reversal leader will be initiated at the end of the decayed branch of the preceding leader. Initial sources of the polarity‐reversal leader are characterized by relatively strong very high frequency power (average value in lightning A, B, and C 24, 18, and 14 dBW) and obvious upward progression. Two of the three upward lightning (lightning A and B) occurred at a normal dipolar charge structure, while the remaining one (lightning C) occurred at an inverted dipolar charge structure. Based on the common features of the polarity‐reversal leader and charge structure, we have proposed a scenario to interpret the process of upward bipolar lightning flashes. Key Points: Initial sources for the polarity‐reversal leader exhibit obvious height ascending and strong radiation power The polarity‐reversal leader is initiated at the end of one decayed branch of the preceding leader Upward bipolar lightning flashes occurred at either a normal dipolar or an inverted dipolar charge structure